Feed restriction since lactation has reduced anxiety in adult Wistar rats - RIUL, Tania Regina; Sousa ALMEIDA, Sebastião (Revista de Nutrição, 2022)
Objective To evaluate the effects of macronutrients (protein, carbohydrate and/or lipid) in the diet of young adult (72 days) and adult (182 days) Wistar rats treated ad libitum and with 30% restriction from birth on anxiety in the elevated plus-maze. Methods We used 238 rats treated from birth, composing the groups: Control, Protein, Carbohydrate, Lipid, Carbohydrate and Lipid, Control Restriction, Protein Restriction, Carbohydrate Restriction, Lipid Restriction and Carbohydrate and Lipid Restriction. The animals were weighed at the beginning and at the end of the experiment and tested in the elevated plus-maze. Data were submitted to analysis of variance, followed by the Newman-Keuls Test (p<0.05). Results Among the animals treated ad libitum, the Control, Carbohydrate plus Lipid and Lipid gained more weight than the Carbohydrate and Protein; ad libitum animals gained more weight than those on restriction; among the restrictions, Carbohydrate Restriction rats were the ones that gained less weight. Diet-restricted animals exhibited reduced first-entry latency, greater percentage of entries and time spent, frequency of open arm extremity visits, head dipping (protected and unprotected), and length of stay in the central area of the elevated plus-maze. The animals with 182 days presented greater latency for first entry, reduced frequency of false entries and visits to the ends of the open arms and protected head dipping. Conclusion Food restricted animals, regardless of the macronutrient present in the diet, were less anxious and/or increased their impulsivity and those at 182 days were more anxious and/or with reduced impulsivity.